Natural H2 Emissions in Colombian Ophiolites: First Findings - Alejandra Carrillo Ramirez; Felipe Gonzalez Penagos; German Rodriguez; Isabelle Moretti (Geosciences, 2023)
The exploration of natural H2 or white hydrogen has started in various geological settings. Ophiolitic nappes are already recognized as one of the promising contexts. In South America, the only data available so far concerns the Archean iron-rich rocks of the Mina Gerais in Brazil or the subduction context of Bolivia. In Colombia, despite government efforts to promote white hydrogen, data remain limited. This article introduces the initial dataset obtained through soil gas sampling within the Cauca-Patia Valley and Western Cordillera, where the underlying geology comprises accreted oceanic lithosphere. In this valley, promising areas with H2 potential were identified using remote sensing tools, in particular vegetation anomalies. The Atmospherically Resistant Vegetation Index (ARVI) appears to be well adapted for this context and the field data collection confirmed the presence of H2 in the soil in all pre-selected structures. The valley undergoes extensive cultivation, mainly for sugar cane production. While H2 emissions lead to alterations in vegetation, unlike reports from other countries, they do not result in its complete disappearance. Soil gas measurements along the thrusts bordering the Cauca Valley also show high H2 content in the fault zones. In the valley, the presence of sedimentary cover above the ophiolites which are presumably the H2 generating rocks, which addresses the possible presence of reservoirs and seals to define potential plays. Drawing parallels with the Malian case, it could be that the intrusive element could serve as seals.